Palladium-coated and bare copper wire study for ultra-fine pitch wire bonding - Lim, A. B. Y. (2013)
There is growing interest in copper (Cu) wire bonding due to its significant cost savings over gold wire. However, concerns on corrosion susceptibility and package reliability have driven the industry to develop alternative materials. Recently, palladium-coated copper (PdCu) wire has become widely used as it is believed to improve reliability. In this paper, we experimented with 0.6 mil PdCu and bare Cu wires. Palladium distribution and grain structure of the PdCu Free Air Ball (FAB) were investigated. It was observed that Electronic Flame Off (EFO) current and the cover gas type have a significant effect on palladium distribution. The Free Air Ball (FAB) hardness was measured and correlated to palladium distribution and grain structure. First bond process responses were characterized. The impact of palladium on wire bondability and wire bond intermetallic using a high temperature storage test was studied. These results for PdCu wire were compared with bare Cu wire.